Prevalence and Risk Factors for Self-Reported Violence of Osaka and Seattle Male Youths. (December 2014) - Bui, Laura; Farrington, David P.; Ueda, Mitsuaki; Hill, Karl G.
Traditionally, Japan has been regarded as a country with low crime. Comparative research has given insights into the extent of similarities and differences in crime between America and Japan. The importance of these studies is the examination of whether Western-established criminological knowledge is applicable to non-Western societies like Japan. Unfortunately, comparative self-report studies involving Japan and investigating youth offending are scarce. The current study investigates risk factors and self-reports of violence from Osaka and Seattle male youths. The findings reveal that Japanese male youths self-report a higher prevalence of violence than Seattle male youths. Risk factors for violence, issues of comparability, and prevalence versus strength of relationships of risk factors are examined. It is concluded that the higher prevalence of violence in Osaka is primarily a function of the higher prevalence of troubled peers and risk taking. The findings call for replication of this type of comparative research.